The phenomenon of private lessons in the basic education stage in light of some variables "A field study for a sample of the first cycle students in Jablah" - يوسف سمر (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research aims to study the phenomenon of the spread of private lessons at the stage of basic education in the Jableh region, and to achieve the goal, the researcher applied a questionnaire to a random sample of 80 students from the first cycle, to identify the reasons for the spread of this phenomenon, and then submit proposals to reduce the degree of its spread. The research found the following: 1-The reasons for the spread of the phenomenon of private lessons can be summed up in several reasons, as the students see them with reasons related to the student himself, the teacher, the applied curriculum, and the family. 2- There are no statistically significant differences between the averages of the respondents of the sample to the questionnaire about the reasons for taking private lessons in the first cycle of basic education according to the sex variables and the system for receiving these lessons (individually or within groups), and also according to the subject variable, while differences were found. On the reasons for taking private lessons according to the student housing variables for the benefit of rural students, as well as the teacher variable for the sample for the benefit of the specialized teacher.